2020
DOI: 10.1101/2020.09.24.312553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 induces double-stranded RNA-mediated innate immune responses in respiratory epithelial derived cells and cardiomyocytes

Abstract: SummaryCoronaviruses are adept at evading and/or antagonizing double-stranded RNA-induced host antiviral pathways, including interferon signaling, OAS-RNase L and PKR while robust cytokine responses characterize severe coronavirus disease. Knowledge of how newly emerged SARS-CoV-2 interacts with these pathways is minimal. SARS-CoV-2 readily infects patient-derived nasal epithelial cells and induced pluripotent stem cell-derived alveolar type 2 cells(iAT2) and cardiomyocytes(iCM). Robust activation of interfero… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 99 publications
12
104
0
Order By: Relevance
“…S6b-e). These data support recent findings indicating SARS-CoV-2 results in an imbalanced host response with a limited interferon response [14][15][16] .…”
Section: Mainsupporting
confidence: 92%
See 1 more Smart Citation
“…S6b-e). These data support recent findings indicating SARS-CoV-2 results in an imbalanced host response with a limited interferon response [14][15][16] .…”
Section: Mainsupporting
confidence: 92%
“…Furthermore, there are few studies examining epigenetic changes associated with coronavirus infection [11][12][13] and none yet published on SARS-CoV-2. However, recent work has demonstrated that SARS-CoV-2 infection induces low interferon expression indicating that it suppresses the innate antiviral host cell response [14][15][16] .…”
Section: Mainmentioning
confidence: 99%
“…The in vitro cell culture and tissue models will also be helpful in studying SARS-CoV-2 infection, cytotoxicity, molecular mechanisms, and drug or therapy effects on cells. As multiple studies have shown, the iPSC-derived cardiomyocytes could be transfected by SARS-CoV-2 and develop cytotoxic effects and death [ 61 , 136 , 137 , 138 , 139 , 140 ]. The use of cardiac organoids will be instructive to mimic COVID-19 infection of the heart but, as of now, there is no study available.…”
Section: Limitations Of Animal Modelsmentioning
confidence: 99%
“…Interestingly, TLR3-deficient mice ( Tlr3 −/− ) did not developed increased blood pressure in response to angiotensin II infusion, suggesting that hypertension is dependent on activation of the TLR3-TRIF [ 31 ]. Another study reported that primary nasal epithelial cells infected by SARS- CoV -2 induced the expression of pluripotent stem cell (iPSC)-derived alveolar type 2 cells (iAT2) and iPSC-derived cardiomyocytes (iCM), which together, represent the host tissues likely affected by clinical SARS- CoV -2 infection, leading to PKR activation as well as viral dsRNA localized to perinuclear foci [ 32 ]. A case report with a 60-year-old man showed unusually rapid development of pulmonary hypertension and right ventricular failure after recent severe COVID-19 pneumonia with cytokine release syndrome [ 33 ].…”
Section: Figmentioning
confidence: 99%
“…In this way, TLR3 activation through dsRNA increases blood pressure associated with several pathological conditions, as mentioned above. Due to the deleterious effects of this response on virus survival, coronaviruses seem to be adept at evading host antiviral pathways induced by viral dsRNA-induced pathways that are essential components of the host innate immune response [ 32 , 37 ]. Therefore, our hypothesis is that the influx of SARS- CoV -2 to the cells [ 38 ] may be over activating the TLR3-related pathway, evoking further damage to the patients, favoring the development of several cardiovascular complications, including hypertension ( Fig.…”
Section: Figmentioning
confidence: 99%